Effect of friction and wear parameters on acrylonitrile butadiene styrene/aluminum-boron carbide-glass spheres polymer composites - TAŞDEMİR, MÜNİR (KAUNAS UNIV TECHNOL, 2014)
In the present work, the friction and wear properties of acrylonitrile butadiene styrene based composites filled with aluminum, boron carbide and glass spheres particles were studied. Fillers contents in the ABS were 5, 10, 15, and 20 wt%. The result showed that the addition of fillers to the composite changed the friction coefficient and wear rate. All specimen wear loss increases with increasing load and sliding distance; meanwhile the friction (static and dynamic) coefficient increases.
Keywords: friction; wear parameters; acrylonitrile butadiene styrene/aluminum-boron carbide-glass spheres polymer composites; TRIBOLOGICAL PROPERTIES; PERFORMANCE; BEHAVIOR